Robust Wnt signaling is maintained by a Wg protein gradient and Fz2 receptor activity in the developing Drosophila wing - Chaudhary, Varun; Boutros, Michael (Development, 2019)
Skip to Next Section - Wnts are secreted proteins that regulate cell fate during development of all metazoans. Wnt proteins were proposed to spread over several cells to activate signaling directly at a distance. In the Drosophila wing epithelium, an extracellular gradient of the Wnt1 homolog Wingless (Wg) was observed extending over several cells away from producing cells. Surprisingly, however, it was also shown that a membrane-tethered Neurotactin-Wg fusion protein (NRT-Wg) can largely replace endogenous Wg, leading to proper patterning of the wing. Therefore, the functional range of Wg and whether Wg spreading is required for correct tissue patterning remains controversial. Here, by capturing secreted Wg on cells away from the source, we show that Wg acts over a distance of up to 11 cell diameters to induce signaling. Furthermore, cells located outside the reach of extracellular Wg depend on the Frizzled2 receptor to maintain signaling. Frizzled2 expression is increased in the absence of Wg secretion and is required to maintain signaling and cell survival in NRT-wg wing discs. Together, these results provide insight into the mechanisms by which robust Wnt signaling is achieved in proliferating tissues.